Dyslipidemia in women: etiology and management - Phan BAP; Toth PP (Dove Medical Press, 2014)
Binh An P Phan,1 Peter P Toth2–41Loyola University Chicago Stritch School of Medicine, Division of Cardiology, Loyola University Medical Center, Maywood, IL, USA; 2CGH Medical Center, Sterling, 3University of Illinois School of Medicine, Peoria, IL, USA; 4Michigan State University College of Osteopathic Medicine, East Lansing, MI, USAAbstract: Dyslipidemia is highly prevalent among women. The management of dyslipidemia is a cornerstone in the prevention of both primary and secondary cardiovascular events, such as myocardial infarction, ischemic stroke, and coronary death. All major international guidelines on the treatment of dyslipidemia recommend similar approaches to the management of dyslipidemia in both men and women. Estrogen replacement therapy should not be considered as a therapeutic option for managing dyslipidemia in women. The reduction of atherogenic lipoprotein burden (reducing low-density lipoprotein cholesterol and non-high-density lipoprotein cholesterol based on risk-stratified thresholds and treatment targets) provided the framework for managing dyslipidemia in the US, Europe, Canada, and elsewhere in the world. Very recently, new guidelines in the US have changed this paradigm, whereby rather than focusing on treatment targets, risk now defines the intensity of treatment with statin therapy, with no specific goals for what level of low-density lipoprotein cholesterol should be attained. It is not clear if this will lead to changes in lipid guidelines in other parts of the world. In the meantime, region-specific guidelines should be followed. Lipid lowering with statin therapy does correlate with reductions in cardiovascular event rates in women. The clinical impact of treating dyslipidemias in women with nonstatin drugs (eg, fibrates, nicotinic acid, bile acid-binding resins, omega-3 fish oils) is as yet not determined.Keywords: dyslipidemia, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, statins